Charge Proportional and Weakly Mass‐Dependent Acceleration of Different Ion Species in the Earth's Magnetotail. Issue 20 (24th October 2017) - Catapano, F.; Zimbardo, G.; Perri, S.; Greco, A.; Delcourt, D.; Retinò, A.; Cohen, I. J.
Abstract: Energetic particles with energies from tens of keV to a few hundred keV are frequently observed in the Earth's magnetotail. Here we study, by means of a test particle numerical simulation, the acceleration of different ion species (H +, He +, He ++, and O n + with n = 1–6) in the presence of transient electromagnetic perturbations. All the considered ions develop power law tails at high energies, except for O + ions. This is strongly correlated to the time that the particle spends in the current sheet. Ion acceleration is found to be proportional to the charge state, while it grows in a weaker way with the ion mass. We find that O 5+/6+ can reach energies higher than 500 keV. These results may explain the strong oxygen acceleration observed in the magnetotail. Key Points: Test particle simulations of the acceleration of different ion species by stochastic fluctuations in the Earth's magnetotail are performed For the top 10% energetic ions, the energy gain grows almost linearly with the ion charge, while the dependence on the ion mass is weaker We propose that the possible presence of O 5+/6+ ions may contribute to explain the strong oxygen energization observed in the magnetotail